Mandibular tumour as the primary manifestation of an occult adenocarcinoma. Issue 1 (7th January 2021) - Kaur, Harpreet; Mishra, Deepika; Manchanda, Smita; Bhutia, Ongkila
Abstract : Oral cavity is an uncommon site for occurrence of metastasis and usually indicates widespread systemic disease. Primary tumours from the lung most commonly metastasise to oral soft tissues (31.3%) and jaw bones (22%) among men. It is quite challenging to diagnose a solitary metastatic lesion and to determine the site of primary lesion, due to the rarity of these occurrences. This case report describes the jaw bone as a first sign of occult primary lung adenocarcinoma with multiple metastases in 47-year-old man. The patient was treated with the combination of carboplatin and paclitaxel, and has completed two cycles till date with a stable clinical course. Diagnosis of metastatic carcinoma of jaw is very challenging. The pathologist must have knowledge of ancillary techniques along with clinical, radiological and histological correlation to determine the origin of distant primary.